PENGARUH CITRA MEREK DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN DI INSPIRED MALANG - Dani Bagus Utomo; Mohammad Hufron; Achmad Agus Priono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT Behavior in consumer purchases is a very interesting subject, because this subject will be concerned with various factors in various human life diverse. And consumer purchasing decisions to buy a product will be greatly influenced by several factors. The phenomenon that attracts the attention of the author and may also attract the attention of many people is the influence of brand image and lifestyle that affect the purchase decision moreover in terms of fashion.This research uses descriptive research. The purpose of this study is to determine whether or not the simultaneous and partial influence between brand image and lifestyle variables on purchasing decisions in Inspired Malang. Subject of this research is all consumer Inspired Malang.Keywords: Brand Image, Lifestyle, Purchasing Decision .